2017
DOI: 10.1038/s41598-017-11585-3
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity in the hypersaline Lake Meyghan, Iran

Abstract: Lake Meyghan is one of the largest and commercially most important salt lakes in Iran. Despite its inland location and high altitude, Lake Meyghan has a thalassohaline salt composition suggesting a marine origin. Inputs of fresh water by rivers and rainfall formed various basins characterized by different salinities. We analyzed the microbial community composition of three basins by isolation and culturing of microorganisms and by analysis of the metagenome. The basins that were investigated comprised a green … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 71 publications
(76 reference statements)
5
61
0
Order By: Relevance
“…Hypersaline ecosystems such as salt lakes are distributed globally, but differ from each other in terms of salt concentration and chemical composition as determined by local geological characteristics (de la Haba, Sánchez‐Porro, Marquez, & Ventosa, ; Naghoni et al, ; Simachew, Lanzen, Gessesse, & Øvreas, ; Tazi, Breakwell, Harker, & Crandall, ). In addition to being hypersaline, these ecosystems are often characterized by other environmental extremes such as high alkalinity, low oxygen concentration and high UV irradiation (Edwardson & Hollibaugh, ; Fernandez et al, ; Javor, ; Naghoni et al, ). Hypersaline lakes offer a unique environment for microbial life and are considered as hot spots of microbial diversity (Ley et al, ; Oren, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hypersaline ecosystems such as salt lakes are distributed globally, but differ from each other in terms of salt concentration and chemical composition as determined by local geological characteristics (de la Haba, Sánchez‐Porro, Marquez, & Ventosa, ; Naghoni et al, ; Simachew, Lanzen, Gessesse, & Øvreas, ; Tazi, Breakwell, Harker, & Crandall, ). In addition to being hypersaline, these ecosystems are often characterized by other environmental extremes such as high alkalinity, low oxygen concentration and high UV irradiation (Edwardson & Hollibaugh, ; Fernandez et al, ; Javor, ; Naghoni et al, ). Hypersaline lakes offer a unique environment for microbial life and are considered as hot spots of microbial diversity (Ley et al, ; Oren, ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, continental thalassohaline lakes that are permanently landlocked with hardly any exchange with the sea have been the focus of a limited number of investigations (Makhdoumi‐Kakhki, Amoozegar, Kazemi, Pašić, & Ventosa, ; Naghoni et al., ). Lake Dziani Dzaha (Mayotte) has been recently classified as a thalassohaline lake and presents several atypical features that make it an excellent model to examine the genetic structure and dynamics of microbial communities across environmental niches (Gérard et al., ; Leboulanger et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Supporting Information Fig. S3, Peñahueca appears in a separate branch within a cluster including the athalassohaline environments Salar Grande (Crits‐Christoph et al ., ), ‘red’ and ‘white’ samples from Meyghan Lagoon (Naghoni et al ., ) as well as the marine saltern at Isla Cristina (Huelva, Spain; Fernandez et al ., ). BLASTN comparisons indicated that only the samples from the Meyghan Lagoon and Salar Grande metagenome presented some similarities (always below 20%) with PH1‐SC.…”
Section: Resultsmentioning
confidence: 99%
“…References: (1) This work; (2) Naghoni et al ., ; (3) Vavourakis et al ., ; (4) Ghai et al ., ; (5) Crits‐Christoph et al ., ; (6) Fernandez et al ., ; (7) Rusch et al ., .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation